CURRENT REGULATIONS AND ANTICIPATIONS ON CRIMINALIZING BLACK CAMPAIGNS FOR THE 2024 REGIONAL HEAD ELECTIONS - Mirzana, Hijrah Adhyanti; Anas, Andi Muhammad Aswin; Rohman, Aditya Dwi (Diponegoro Law Review, 2024)
Campaigning plays a critical role in elections, enabling candidates to present their vision, mission, and programs to the public. However, Law Number 8 of 2015, lacks explicit regulations on black campaigning, especially when it occurs via electronic media. This research highlight the Regional Head Election Law only indirectly addresses defamation in Article 69 (b) and (c), which prohibits insults targeting individuals, religions, ethnicities, races, groups, and candidates. Other relevant regulations, such as the Criminal Code and the ITE Law, contain provisions on defamation, hate speech, and incitement, but they are not spesifically regulate in the context of election. This paper examines the urgency of reformulating explicit prohibitions and criminalization of black campaigning within the Regional Head Election Law. Using a normative juridical approach to examines the existing regulations, this research suggests that an amendment to the Regional Head Election Law is necessary to explicitly define and prohibit black campaigning, establishing it as a formal offense and identifying relevant legal subjects. By setting clear prohibitions, this reform would strengthen fairness and integrity in elections, prevent the spread of false information and incitement, and align with the principle of legality, ultimately enhancing the democratic process.